Incidence trends and survival of metastatic prostate cancer with bone and visceral involvement: 2010-2019 surveillance, epidemiology, and end results - Kadeerhan, Gaohaer; Xue, Bo; Wu, Xiao-Lin; Chen, Wei-Nan; Wang, Dong-Wen (Frontiers in Oncology, 2023)
Background: The incidence of prostate cancer (PCa) has continued to increase since the US Preventive Services Task Force (USPSTF) recommendations against prostate-specific antigen (PSA)-based screening for all men in 2012, approximately half of additional diagnosed cases are advanced-stage, including regional PCa and metastatic PCa (mPCa). It is very important to investigate the shift in mPCa incidence and mPCa-related mortality risk, as the survival of mPCa remains poor. Objective: To investigate the incidence temporal trend of mPCa stratified by metastatic site, including bone and visceral metastatic involvement, and potential survival improvements. Materials: Based on the recently released Surveillance, Epidemiology, and End Results (SEER) data (2010-2019), the age-adjusted incidence rates of mPCa with bone and visceral involvement with annual percentage changes (APCs) were assessed by a joinpoint regression model in men aged 45 years and older by age and race groups, and potential recent improvements in overall survival (OS) and cancer-specific survival (CSS) were estimated by the Kaplan‒Meier method and Cox regression model. Results: From 2010 to 2019, a total of 19081 (84.8%) and 3413 (15.2%) mPCa patients with bone and visceral involvement, respectively, were recorded in the SEER database. Considering all races and age groups, the incidence rate of mPCa with bone metastasis remained stable during 2017-2019 (APC, 0.9%; p=0.421) after increasing during 2010-2017 (APC, 5.8%; p<0.001). For visceral metastasis, the incidence rate increased by 12.3% (p<0.001) per year from 2010-2019. Non-Hispanic Black men have higher incidence rates than other populations, and the Non-Hispanic Black to Non-Hispanic White incidence rates ratios of mPCa declined with the greater increasing pace of incidence of Non-Hispanic White men. There was a slight improvement in both OS and CSS among men with bone and visceral metastasis involvement when comparing the 2013-2016 period to the pre-2013 period. Conclusion: Our findings show that the incidence of mPCa with bone and visceral involvement has increased in recent years and that there has been a potential improvement in survival. Future efforts are still needed to watch closely if the rising incidence trends continue.